Clinical analysis of laparoscopic pyeloplsty for ureteropelvic junction obstruction in infants under 3 months old - Bian, Zedong; Xiong, Geng; Liu, Tong; Zhi, Yong; Liu, Ming (Frontiers in Pediatrics, 2026)
BackgroundTo evaluate the safety and efficacy of laparoscopic pyeloplasty (LP) in treating ureteropelvic junction obstruction (UPJO) among infants under 3 months of age.MethodsA retrospective analysis was performed on 45 infants with hydronephrosis caused by UPJO treated with LP between January 2019 and December 2024. Patients were divided into two groups by age: 25 infants aged 0–3 months (Group A) and 20 infants aged 4–12 months (Group B). Operative time, hospital stay, complications, anterior–posterior renal pelvic diameter (APD), and minimum renal cortex thickness (Min.RCT) were compared.ResultsAll procedures were completed laparoscopically without conversion to open surgery. No significant differences were observed between groups in operative time, postoperative hospital stay, complication rates, postoperative APD, or postoperative Min.RCT. Both groups showed significant improvement in APD reduction and Min.RCT increase compared with baseline. During follow-up (6–63 months, median 38.65), no recurrence or reoperation was required.ConclusionsLP is a safe and effective treatment for UPJO in infants ≤3 months with surgical indications.